PENGARUH ELECTRONIC WORD OF MOUTH (EWOM) DAN KEAMANAN TERHADAP KEPUTUSAN MENGGUNAKAN FITUR DANA GOALS PADA DOMPET DIGITAL DANA - Mega Febriyanti, Ni Made; Mirati, R. Elly; Purwaningrum, Endang (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research is in the background of numerous cases of losing the balance of DANA users and placing DANA goals features that are not located on the main page of the DANA application so that the users do not know the advantages of the feature. This research aims to investigate how the influence of electronic word of mouth and security on user decisions in using DANA goals on DANA applications and to test the hypothesis whether free variables are electronic word of mouth and safety influence on bound variables that use DANA goals features. n this study, sampling techniques are purposive samplings with criteria that respondents are users of the DANA goals feature. This research uses primary data through the distribution of questionnaires to 100 respondents. Double linear regression analysis with the help of SPSS version 26 is the method of analysis used. The results of this study show that partly electronic word of mouth and security have a positive and significant influence on decisions using the DANA goals feature. In addition, simultaneous tests also show that electronic word of mouth and safety jointly positively and significantly influence decisions using DANA goals feature.